ANALISIS KUALITAS PRODUK, DESAIN, DAN KARAKTERISTIK TERHADAP MINAT BELI RUMAH PADA PT SUMUT CITRA TIARA MEDAN - Ocdy Amelia (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2021)
This study aims to determine the extent of the influence of product quality, design, and characteristics on buying interest at PT Sumut Citra Tiara Medan either partially or simultaneously. The problem discussed in this study is whether it has a positive and significant effect on Product Quality, Design and Characteristics on Interest in Buying a Type 36 House at PT Sumut Citra Tiara Medan. The data used is primary data obtained directly through the distribution of questionnaires with a total of 171 customers respondents, documentation studies, library research, and observation. The author uses multiple linear regression analysis techniques with the help of SPSS 16.00 software to process the data first by conducting data tests, f tests, and hypothesis testing. The results of the analysis show the Adjusted R Square value of 7% by product quality, design and characteristics, while the rest is 93% is influenced by other variables not examined in this study.